Plasma metabolic profiles of elite rowers response to the early phase of altitude training based on LC-MS - Gao, H.; Gao, B.-H.; Meng, Z. (Exercise Biochemistry Review, 2018)
Objective When arriving at altitude, because of the dry air, strong ultraviolet and especially the low oxygen et.al., athletes who living on the plain always exhibited kinds of stress reactions such as hyperventilation, tachycardia, dizziness, sleep-disorder, gastrointestinal disturbance and cognitive impairment in the early phase. Except these stress reactions, some studies reported the carbohydrate and lipid metabolism show significant change. Acute exposure to hypoxia could strengthen the glycolysis and suppress hepatic gluconeogenesis. The expression of some genes involved in lipid oxidation was down-regulated. However, it`s also found the increased activity of some enzymes took part in aerobic metabolism in muscle after long term acclimatization to altitude. These inconsistent conclusions make us confusion. Train load is an important factor influence the stress reactions which isn`t like as altitude travel for normal people. What would happen in the body of athletes when altitude training? We still know very little. Metabonomic give us a new tool to understand the whole map of body`s reaction to altitude training. In this pilot study, we aimed to explore the plasma profiles changes of elite rowers in the early two-weeks training at 2300m plateau using metabolic tool based on LC-MS.